NILAI KOEFISIEN LIMPASAN (C) SUB DAS TARIPA DI KECAMATAN TOAYA KABUPATEN DONGGALA PROVINSI SULAWESI TENGAH - Paramitha, Tirtha Ayu; Rauf, Abdur (Universitas Tadulako, 2018)
The coefficient of surface runoff (denoted by C), in this case is strongly influenced by the watershed conditions such as gradients, soil infiltration, land use and surface water deposits. This value of C can be used as an indicator in assessing the level of damage of the watershed. Forest and land of Taripa sub-watershed in taripa village is functioned as a regulator of hydrology and also a source of water for irrigation in Sumari village, Lero and Toaya. The Taripa sub-watershed has a very important role for life. To know the tendency of hydrological characteristic of Taripa sub-watershed is better or worse, it can be investigated by observing the tendency of Taripa sub-watershed flow by calculating the runoff coefficient value (C). To calculate the runoff coefficient value, firstly the water discharge and rainfall is analyzed.This research was conducted with the aim to know the value of runoff coefficient (C) and the its function (C) of Taripa sub watershed in Taripa Village of Donggala Regency of Central Sulawesi Province. This research was planned to be implemented from September 2016 until April 2017 in Taripa Village of Toaya District of Donggala Regency, Central Sulawesi Province. The results of this study are expected to be an early information of the condition of land capability of sub-watershed Taripa in order to control the water by knowing the runoff coefficient value (C). Based on the results of the research, the daily debit value is the total of daily debit, 523,048,50 m3 reduced by the Base Flow, 78,697 m3 equals to 442,157,5 m3 with rainfall totaled 163 mm, where the highest rainfall happened on Tuesday, June 13, 65 mm, and on Wednesday, 21 June, 27 mm. The value of runoff coefficient (C) of Taripa river, based on the calculation, is 0.37. This value illustrates that the hydrologic system in the Taripa sub watershed of Taripa Village is in moderate level.